Development of an in vitro neuroblastoma 3D model and its application for sterigmatocystin-induced cytotoxicity testing. (November 2021) - Zingales, Veronica; Torriero, Noemi; Zanella, Luca; Fernández-Franzón, Mónica; Ruiz, Maria-José; Esposito, Maria Rosaria; Cimetta, Elisa
Abstract: Given the increasing importance of establishing better risk assessments for mycotoxins, novel in vitro tools for the evaluation of their toxicity are mandatory. In this study, an in vitro 3D spheroid model from SH-SY5Y cells, a human neuroblastoma cell line, was developed, optimized and characterized to test the cytotoxic effects caused by the mycotoxin sterigmatocystin (STE). STE induced a concentration- and time-dependent cell viability decrease in spheroids. Spheroids displayed cell disaggregation after STE exposure, increasing in a dose-dependent manner and over time. STE also induced apoptosis as confirmed by immunofluorescence staining and Western blot. Following the decreased proliferation and increased apoptosis, STE cytostasis effects were observed by migration assays both in 2D and 3D cell culture. Increased ROS generation, as well as DNA damage were also observed. Taken together, these data highlight the cytotoxic properties of STE and suggest that cell culture models play a pivotal role in the toxicological risk assessment of mycotoxins. The evaluation of cytotoxicity in spheroids (3D) rather than monolayer cultures (2D) is expected to more accurately reflect in vivo -like cell behaviour. Highlights: Sterigmatocystin (STE) toxicity was evaluated in spheroids of neuroblastoma cells. STE induced higher mortality in SH-SY5Y spheroids than SK-N-DZ spheroids. STE induced oxidative stress, apoptosis and DNA damage in 3D SH-SY5Y cells. Cytostasis effects were mainly observed in 2D and 3D SH-SY5Y cells exposed to STE. Results obtained in spheroids provided a more realistic portrait of STE toxicity.